Urban planning in Guanabara State, Brazil: Doxiadis, from Ekistics to the Delos Meetings - Rezende, Vera F. (International Planning History Society Proceedings, 2016)
The work carried out by researchers in the urbanismo.br research network encompasses objects and the creation of frameworks, hypotheses and documents and is based on three premises: urbanization and development, urbanization and planning, and institutions. The theme related to planning (this panel) has been conducted by three researchers : Maria Cristina da Silva Leme , Fabio José Martins de Lima and Vera F. Rezende. The use of nucleation as a resource does not mean entirely discrete approaches, but rather a strategy to improve our understanding of changes in the field of urbanism and urban planning during a period of profound political transformation. The period chosen for the research is the 1960s, and we have taken into consideration the period’s setbacks and advances in accordance with the object of each piece of research. We have identified inflections, continuity and ruptures in the concepts and tendencies of the urbanism adopted in plans for different government spheres and different territorial scales and which guided the teams involved. There was increased and more complex team building, both in public bodies and in the local and foreign consultancies hired for such purposes. The conception of urban planning as a response to the unequal conditions of development that surfaced in the immediate post-war period was adapted to the policies of the new authoritarian era. We have also identified changes to the urban structuring process during the periphery expansion of Brazilian cities in the 1940s and 1950s. These changes were prompted by housing policies and investment in large infrastructure projects that redefined growth pivots and reaffirmed the new metropolitan regional character. This panel will debate the urban policies adopted by cities/thermal spas in Minas Gerais state amid the modernization of these cities before and after the 1964 military coup. We will also discuss the creation and modus operandi of the urban and regional planning offices and teams in the 1960s, especially in São Paulo. This analysis also looks into how the professional and political trajectories of the technicians that comprised the teams in these offices reveal the different concepts and trends in urbanism adopted in the various Plans drawn up for different government spheres. We also analyze how the Ekistics Theory (which was formulated by Constantinos A. Doxiadis) was applied to the Plan for Guanabara State, which was concluded in 1965. Following the Delos Meetings, this theory subsequently evolved into the concept of Network, which was based on the idea of complex relations in human activity networks and how they apply to different fields of knowledge, especially architecture and urbanism. In this research, we analyze the association between planning and authoritarian and repressive practices and the complexity behind these relations. We will observe tensions, ruptures and continuity in particular.